The Influence of E-Marketing and Product Quality on Purchase Decisions with Brand Awareness as an Intervening Variable in Wardah Skincare Products in Jember - Nevia, Yayah Ikhda; Supeni, Retno Endah; Suharsono, Riyanto Setyawan (International Journal of Multidisciplinary Sciences and Arts, 2025)
Promotions have a great effect on business efforts to increase sales and market a product. In promoting products, quality is also an important factor to produce products that can attract consumer interest. This study aims to determine the influence of promotion and product quality on Wardah skincare purchase decisions in Jember, with brand awareness as an intervening variable. The research method used a quantitative approach by distributing questionnaires to 100 respondents who were followers of the Wardah TikTok account. Data analysis used SPSS version 26 through validity, reliability, multiple linear regression, t-test, f-test, and determination coefficient. The results of the study show that promotion and product quality have a significant effect both partially and simultaneously on purchase decisions. Brand awareness has also been shown to mediate the relationship between promotion, product quality, and purchase decisions. This study aims to analyze the influence of E-Marketing and Product Quality on Purchase Decisions with Brand Awareness as an intervening variable. In the digital era, E-Marketing plays an essential role in shaping consumer behavior, while product quality remains a key factor that determines customer satisfaction and loyalty. This research seeks to examine how these two variables affect consumers’ purchase decisions, both directly and indirectly through the level of brand awareness. The study uses a quantitative research approach. Data were collected through online questionnaires distributed to 100 respondents who had made online purchases within the past six months. The collected data were analyzed using multiple linear regression and path analysis with the help of SPSS software. The results indicate that E-Marketing and Product Quality each have a positive and significant influence on Brand Awareness. Additionally, Brand Awareness has a positive and significant effect on Purchase Decisions. The findings also show that Brand Awareness partially mediates the relationship between E-Marketing, Product Quality, and Purchase Decisions. These results suggest that improving digital marketing strategies and maintaining high product quality can effectively increase brand awareness, which in turn enhances consumer purchase decisions. Therefore, companies should focus on integrating E-Marketing efforts with consistent product quality to strengthen their brand position in a competitive digital marketplace.